The Prevalence of Low Back Pain among Nurses in Yazd, Southeast Iran - Abolfazl Barkhordari; Gholamhossain Halvani; Mahdi Barkhordari (International Journal of Occupational Hygiene, 2013)
Musculoskeletal disorders (WMSDs) are of serious concern to many organizations, including health care centres. Low back pain (LBP) with no clinical cause is common in nurses. This study aimed to assess the prevalence rate of LBP in nurses. This descriptive, cross-sectional study was carried out on a population of 351 nurses from educational hospitals of Yazd University of Medical Sciences; Yazd, Iran aged 20-45 years. Information on these potential risk factors for LBP was sought using a translated Nordic questionnaire. Two hundred sixty respondents (74.3%) reported experiencing pain at least in one of their nine body regions during last year. The highest prevalence of LBP was seen among nurses in orthopaedic surgery (80.6%), operation room (79.2%), neurology (75.3%) and general surgery (73.7%), emergency medicine (69.9%), paediatrics (59.2%), obstetrics and genecology (54.3%), internal medicine (52.7.5%), intensive care unit (51%), ENT (50.4%), and infectious disease (48%) sections, respectively. These findings suggest that hospitals should focus and attempt to improve the ergonomics of nursing activities. In addition, effective methods of implementing changes in work systems are needed.